The Chain of Value Analysis of Organic Coffee Bean Aroma in Keke Koka Products Rambipuji Subdistrict Jember Regency Indonesia - Rallyanta Tarigan; Esra Frandika Karo-Karo (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Indonesia is among the world's foremost coffee producers, with robusta beans from Jember Regency playing a substantial role in national production. This study examines the value chain of natural coffee beans in Keke Koka, an agroindustry in Rambipuji District, Jember Regency, East Java, Indonesia. A qualitative descriptive methodology was utilized, including purposive sampling, with Keke Koka designated as the sole coffee-based fragrance processor in the area. Data were gathered from January to March 2025 via interviews with the business owner, five production workers, and pertinent institutions, supplemented by observations and secondary sources. The research objectives were evaluated utilizing Porter's Value Chain Analysis framework to investigate the elements of primary and support activities. The results identify three primary participants: 1) PUSLITKOKA, a supplier of premium robusta coffee beans; 2) Keke Koka, which undertakes the processes of roasting, fermenting, and aroma mixing; and 3) A network of local and interregional distributors that enhances market penetration. Supporting institutions, such as the Cooperative Office and the Industry and Trade Office, offer training, quality assurance guidance, and certification facilitation. The collaboration among these entities produces a specialized product that gains a competitive advantage from local resources and innovation. Nonetheless, the firm faces obstacles, including outdated technology, limited digital marketing efforts, and insufficient product certification. Recommendations include sustaining collaboration with PUSLITKOKA, implementing advanced processing technologies, enhancing digital marketing strategies, and obtaining halal and BPOM certification. This research enhances understanding of rural agroindustrial value chains and provides pragmatic insights to improve the competitiveness of small-scale agroindustries in coffee-producing areas.